2011
DOI: 10.1158/1535-7163.mct-11-0100
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Chemical Biology Approach Identifies Specific Vulnerability of Ewing's Sarcoma to Combined Inhibition of Aurora Kinases A and B

Abstract: Ewing's sarcoma is a pediatric cancer of the bone that is characterized by the expression of the chimeric transcription factor EWS-FLI1 that confers a highly malignant phenotype and results from the chromosomal translocation t(11;22)(q24;q12). Poor overall survival and pronounced long-term side effects associated with traditional chemotherapy necessitate the development of novel, targeted, therapeutic strategies. We therefore conducted a focused viability screen with 200 small molecule kinase inhibitors in 2 d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 46 publications
(59 reference statements)
1
25
0
Order By: Relevance
“…Aurora kinase inhibitors are in clinical trials in hematologic malignancies and solid tumors (27) and are in Phase II clinical trials in a broad spectrum of adult soft tissue sarcoma. Preclinically, pediatric sarcoma are sensitive to aurora kinase inhibitors; however, clinical trials have not yet been initiated (28). In pediatric sarcoma xenograft studies, alisertib (NSC759677) had activity in rhabdomyosarcoma xenografts but little activity against Ewing sarcoma xenografts (29); however, higher doses higher than can be achieved in humans were used (30).…”
Section: Discussionmentioning
confidence: 99%
“…Aurora kinase inhibitors are in clinical trials in hematologic malignancies and solid tumors (27) and are in Phase II clinical trials in a broad spectrum of adult soft tissue sarcoma. Preclinically, pediatric sarcoma are sensitive to aurora kinase inhibitors; however, clinical trials have not yet been initiated (28). In pediatric sarcoma xenograft studies, alisertib (NSC759677) had activity in rhabdomyosarcoma xenografts but little activity against Ewing sarcoma xenografts (29); however, higher doses higher than can be achieved in humans were used (30).…”
Section: Discussionmentioning
confidence: 99%
“…Aurora kinase A and B are overexpressed in various sarcomas, including chondrosarcoma, osteosarcoma, synovial sarcoma, and Ewing sarcoma, and are associated with poor prognosis and metastasis 104107 . Targeting aurora kinase A and B with small molecule kinase inhibitors, shRNA, and siRNA exhibited inhibition of tumor cells 105, 107 . Moreover, a study demonstrated that the combination of aurora kinase A and B kinase inhibitor VX-680 (Tozasertib) with etoposide and doxorubicin showed synergistic effects in Ewing sarcoma 107 .…”
Section: Targeting Serine/threonine Protein Kinases To Reverse Mdr Inmentioning
confidence: 99%
“…Targeting aurora kinase A and B with small molecule kinase inhibitors, shRNA, and siRNA exhibited inhibition of tumor cells 105, 107 . Moreover, a study demonstrated that the combination of aurora kinase A and B kinase inhibitor VX-680 (Tozasertib) with etoposide and doxorubicin showed synergistic effects in Ewing sarcoma 107 . Recently, another report also confirmed that the combination of VX-680 with cisplatin, doxorubicin, and methotrexate exhibited a synthetic lethal interaction in osteosarcoma cell lines.…”
Section: Targeting Serine/threonine Protein Kinases To Reverse Mdr Inmentioning
confidence: 99%
“…When we checked in detail, however, none of the PKC412 targets we detected by chemoproteomics was found in the mitochondria-related gene expression datasets shown to be altered by doxycycline (42). Prior to LC-MS/MS analysis, drug pull-down samples from both A673 wt and EWS-FLI1 knockdown conditions were verified by immunoblotting for the presence of Aurora kinase A (AURKA), a known target of PKC412 and one of the kinases upregulated by the EWS-FLI1 oncoprotein (43). Although present in the lysates at a moderate level, AURKA was not detected in the pulldown experiment from EWS-FLI1 silenced cells ( Supplementary Fig.…”
Section: Identification Of a Ewing Sarcoma Specific Synergy Between Pmentioning
confidence: 99%